The law of curvilinear disparities revisited: the case of the Portuguese political parties - Belchior, A. (2017)
May’s law of curvilinear disparity (1973), which argues the intermediate leadership strata in parties assume more radical political positions compared to both the party leaders and the electorate, has been tested in diverse contexts, often repeated and mainly refuted. However, of these tests of the law not one has included a profound and comparative analysis of the Portuguese political parties. The aim of this article is to fill this lacuna and to ascertain to what extent May’s law is valid for understanding the ideological and political representation of the two main Portuguese parties: the Socialist Party (PS – Partido Socialista) and the Social Democratic Party (PSD – Partido Social Democrata). In both cases the positions of deputies in the national parliament and their respective electorate are compared with an intermediate stratum of political activists. We will see, first, that the law is almost entirely applicable when it is used an indicator of self-positioning on the left-right scale. Second, that the Law has greater applicability in terms of this political division than it does in relation to socio-economic issues or to “new politics” issues. Third, in the case of socio-economic issues, the law’s applicability is much greater within the PS, while in the case of “new politics” it is more applicable within the PSD.